Comparative Study of Chemical Stability of Two H1 Antihistaminic Drugs, Terfenadine and Its In Vivo Metabolite Fexofenadine, Using LC-UV Methods. (2nd April 2019) - Gumieniczek, Anna; Berecka-Rycerz, Anna; Pietraś, Rafał; Kozak, Izabela; Lejwoda, Karolina; Kozyra, Paweł
Abstract : A comparative study of chemical stability of terfenadine (TER) and its in vivo metabolite fexofenadine (FEX) was performed. Both TER and FEX were subjected to high temperature at different pH and UV/VIS light at different pH and then quantitatively analyzed using new validated LC-UV methods. These methods were used to monitor the degradation processes and to determine the kinetics of degradation for both the compounds. As far as the effects of temperature and pH were concerned, FEX occurred more sensitive to degradation than TER. As far as the effects of UV/VIS light and pH were concerned, the both drugs were similarly sensitive to high doses of light. Using all stress conditions, the processes of degradation of TER and FEX followed the first-order kinetics. The results obtained for these two antihistaminic drugs could be helpful in developing their new derivatives with higher activity and stability at the same time.